Peran Penting Pencatatan Akuntansi Di Kampung Wisata Kuliner Mayangsari Semarang - Ratna Herawati; Masitha Fahmi Wardhani; Linda Ayu Oktoriza; Diana Puspitasari; Amalia Nur Chasanah; Dian Indriana Hapsari (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
The Mayangsari culinary tourism village Semarang was formed in 2018 by a number of people who are members of the Putra Mayangsari Disaster Preparedness Group (KSB Puma) and the Mayangsari Tourism Awareness Group (Pokdarwis Mayangsari). The Semarang City Culture and Tourism Office provided ideas for developing Mayangsari River Tourism by highlighting the potential attractions of river tubing, river education and culinary tourism. The development of the Mayangsari culinary tourism village, which is a finalist in the 2022 great village competition in the creative and innovative village category, still has several things that need to be improved, especially regarding accounting records for culinary tourism. Based on this, it is important to provide education on the importance of accounting records in theory and practice in the Mayangsari culinary tourism village. The approach used in this community partnership program is in the form of giving lectures and tutorials by providing accounting material ranging from recording to preparing financial reports. It is hoped that this community partnership program will increase and sustain economic activities in the Mayangsari culinary tourism village.